2019
DOI: 10.1051/e3sconf/20199102004
|View full text |Cite
|
Sign up to set email alerts
|

3D-flexible intumescent fire protection mesh for building structures

Abstract: The increased operational properties, main of which - ensuring fire resistance in the conditions of the hydrocarbon mode of the fire, resistance to low temperatures and lack of wet processes at installation are necessary for means of fire protection of structures of buildings and constructions of an oil and gas complex. The review of means of fire protection of new type - the constructive bent fire protection which advantage is the set of positive characteristics as constructive fire protection (a plate, a she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…For example, in [20], tests of steel structures with structural fire protection on the example of super-thin basalt fibers in the Arctic region were demonstrated; the evaluation of various means of fire protection was carried out, the results of which showed that the most effective coatings for harsh Arctic conditions are materials containing super-thin basalt fibers. In [21], studies on structural fire protection used to increase the fire resistance limit of building structures used in oil and gas facilities are presented. Intumescent coatings based on epoxy binders, which have resistance to chemical and climatic influences, and, when the temperature rises, swell up, forming a foamcoke that protects the structure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in [20], tests of steel structures with structural fire protection on the example of super-thin basalt fibers in the Arctic region were demonstrated; the evaluation of various means of fire protection was carried out, the results of which showed that the most effective coatings for harsh Arctic conditions are materials containing super-thin basalt fibers. In [21], studies on structural fire protection used to increase the fire resistance limit of building structures used in oil and gas facilities are presented. Intumescent coatings based on epoxy binders, which have resistance to chemical and climatic influences, and, when the temperature rises, swell up, forming a foamcoke that protects the structure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in [10], experiments concerning steel structures with structural fire protection using basalt superfine fibers as an example in the Arctic region were demonstrated; an assessment of various fire protection means was conducted, the results of which showed that the most effective coatings for severe Arctic conditions are materials containing basalt superfine fibers based on basalt superfine fibers. In [14], research on structural curved fire protection to increase the fire resistance limit of building structures used at oil and gas facilities was presented.…”
Section: Introductionmentioning
confidence: 99%